Agrotechniques for including plagiotrops in black pepper (piper nigrum L) - Ramnarace Sukhna (Department of Plantation Crops and Spices, College of Horticulture, 2014)
The investigations on “Agrotechniques for inducing plagiotrops in black pepper (Piper nigrum L.)” were conducted under three experiments at the pepper research unit attached to the Department of Plantation Crops and Spices, College of Horticulture, Kerala Agricultural University Main Campus, Vellanikkara during 2012-2014. The first experiment was carried out with an objective to elucidate the effects of treatments T1 - IBA 1000 ppm, T2 - cow dung slurry, T3 - tender coconut water, T4 - two per cent sugar and T5 - charcoal paste in enhancing sprouting and root characters in two to three node semi hard wood orthotropic and runner shoots. The effect of different treatments on sprouting was varying in different months. The minimum time recorded from planting to initiation of sprouting in orthotrops and runners was 17 days. Maximum sprouting was observed on 21 and 28 days after planting in runners and orthotrops respectively. There was no significant difference among the treatments with respect to the length of primary roots, number of secondary roots/ plant, weight of roots (g), volume of roots (ml) and number of leaves/ plant in runners and orthotrops. The second experiment was aimed at evaluating rooted orthotrops and runners in the field. Three months old rooted orthotrops and runners planted in the field showed that the height at which first lateral was produced was much lowered in orthotrops than runners. However plant spread was better in runners. The third experiment was conducted to study the influence of pruning, tipping and lowering on the growth of black pepper. Pruning carried out six months after planting showed that unpruned plants produced more number of orthotropic shoots in both Panniyur 1 and 2. Pruning at ten months after planting did not have significant effect on the number of orthotropic shoots produced both in Panniyur 1 and Panniyur 2. When pruning was done six months and ten months after planting, the height at which first lateral was produced was much lower in pruned plants compared to the unpruned plants. Tipping immediately after planting had a negative effect on the number of orthotropic shoot produced and plant spread. However, the height at which first lateral was produced was lower in tipped plants compared to the untipped plants but the difference was not significant. When tipping was carried out three months after planting there was significant lowering of height at production of first lateral but plant spread was more in untipped plants. Lowering had significant positive effect on number of orthotropic shoots produced and plant spread in both Panniyur 1 and Panniyur 2.